2019
DOI: 10.1007/s10921-019-0647-9
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Automated Eddy Current Detection of Cracks in Steel Plates

Abstract: Applying life estimation approaches to determine in-service life of structures and plan the inspection schedules accordingly are becoming acceptable safety design procedures in aerospace. However, these design systems shall be fed with reliable parameters related to material properties, loading conditions and defect characteristics. In this context, the role of nondestructive (NDT) testing reliability is of high importance in detecting and sizing defects. Eddy current test (ECT) is an electromagnetic NDT metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Nishimizu [11,12] detected cracks in a non-ferromagnetic material using an arrayed multi-coil probe with two scanning angles and demonstrated that the sensitivity was affected by the two angles. Mohseni [13] investigated the scanning angle for a ferromagnetic material with a split D-probe and found that the signal amplitude varied with the scanning angle. The changing trend for ferromagnetic material is opposite that for non-ferromagnetic material.…”
Section: Introductionmentioning
confidence: 99%
“…Nishimizu [11,12] detected cracks in a non-ferromagnetic material using an arrayed multi-coil probe with two scanning angles and demonstrated that the sensitivity was affected by the two angles. Mohseni [13] investigated the scanning angle for a ferromagnetic material with a split D-probe and found that the signal amplitude varied with the scanning angle. The changing trend for ferromagnetic material is opposite that for non-ferromagnetic material.…”
Section: Introductionmentioning
confidence: 99%
“…An eddy current sensor is considered for manual inspection in this study. The POD curve of the eddy current sensor for a crack-like defect is obtained from existing literature for an eddy current sensor by Mohseni et al 36 where its detection capabilities are evaluated experimentally with qualified inspectors and fitted to a logistic function. Though this POD study was done on steel plate structures instead of pipes, it provides a reasonable estimate on the typical detection capabilities of an eddy current sensor.…”
Section: Description Of the Inspection And Monitoring Schemesmentioning
confidence: 99%
“…What poses a real challenge is the determination of complex eigenvalues when the region under consideration consists of several sub-regions (containing conductive material or air). Such a situation occurs when modeling disks [ 8 , 9 , 10 , 11 ], tubes [ 12 , 13 , 14 , 15 , 16 ], rods [ 17 , 18 ], materials with a defect [ 19 , 20 , 21 , 22 , 23 , 24 ], and wherever there are edges [ 25 , 26 , 27 , 28 , 29 ] or discontinuities [ 30 , 31 , 32 ] ( Figure 1 ). Determination of the eigenvalues then boils down to finding complex roots of the appropriate complex function.…”
Section: Introductionmentioning
confidence: 99%